Peran Pondok Pesantren Dalam Pencegahan Radikalisme - Abdullah Gousul Fu’ad (Journal of Society and Development, 2022)
Radicalism is a movement in the form of a movement to replace or change the old ideology into a new ideology that appears in Islam internally. This study aims to be able to find out descriptively about the role of pesantren in preventing radicalism. This article uses data collection techniques in qualitative research is through library research. The literature research in this study needs to strengthen the analysis of research related to the efforts of pesantren in preventing radicalism. Islamic boarding school is a form of educational institution that has existed for a long time in Indonesia and has been proven to have a major contribution in various aspects of the nation's life from the Kingdom period to resistance to colonialism. The term Islamic boarding school according to scientists are two terms that contain one meaning. that the pesantren has a guideline "Al-Muhafazah'ala al-qadim as-shalih wa al-akhdzu bi al-jadid al-ashlah" which means maintaining good old traditions and adopting new, better traditions, that things that are acceptable and beneficial for Islam in life, it needs to be developed. While things that are not allowed are things from outside that are contrary to or harmful to Islam